"A Curious Inconsistency": The Discourse of Social Work on the 1922 Married Women's Independent Nationality Act and the Intersecting Dynamics of Race and Gender in the Laws of Immigration and Citizenship. (November 2015) - Park, Yoosun
The Cable Act of 1922 provided for the first time in U.S. history, independent citizenship for married women. Henceforth, a woman's citizenship was a status separate from her husband's. A victory for activists, including many prominent social workers who had long-pursued equal political status for women, the Cable Act benefited many but not all women. Using primary archival data and published social work writings from the era, this study analyzes how prominent immigrant-serving social workers responded to the Cable Act, and the bifurcated sets of raced and gendered biases that shaped this and other policies and practices of immigration and citizenship.